Patient response to sleep apnea screening in a dental practice. (23rd June 2016) - Dillow, Kristin; Essick, Gregory; Sanders, Anne; Sheats, Rose; Brame, Jennifer
Abstract: Objective: This study investigated patient response to a recommendation for physician evaluation following screening for obstructive sleep apnea (OSA) in a dental practice. Methods: In a community‐based dental practice in Raleigh, North Carolina, 119 patients were recruited by nonprobability purposive sampling and administered both a validated subjective (STOP questionnaire) and objective (pulse oximeter) screening instrument for OSA. Patients who screened high‐risk for OSA on either instrument were recommended to consult their physician within three months. All patients were contacted via telephone after three months to determine if they had consulted a physician regarding their screening results. Multivariate log‐binomial models estimated prevalence ratios (PR) and 95 percent confidence limits (95% CL) for physician consultation according to OSA risk, adjusting for potential confounders. Results: Overall, 18.5 percent of patients screened high‐risk on the STOP questionnaire alone, 26.1 percent on pulse oximetry alone, and 31.9 percent on both instruments. Follow‐up of 111 subjects (93.3%) found that 40 (47.1%) of those high‐risk for OSA on one or both instruments sought physician evaluation. Patients who screened high‐risk on pulse oximetry were 2.55 times as likely to seek physician evaluation compared with those who screened low‐risk on both instruments (PR = 2.55, 95% CL: 1.02, 6.37). Screening high‐risk on the STOP questionnaire did not significantly increase the likelihood of physician evaluation. Conclusions: Nearly, half of dental patients who screen high‐risk for OSA may be responsive to a recommendation to seek physician evaluation.